Quantification of camptothecin and some flavonoids from Ixora javanica (Blume) DC by HPLC - Ghoshal, Dipanwita S.; Ganesan, Gokul; Kharat, Sopan N.; Godbole, Sangeeta A. (Current Botany, 2025)
Ixora javanica is a medicinally important plant reported to show anticancer, anti-inflammatory, antioxidant and hepatoprotective activities. The present study investigates four medicinally important phytoconstituents present in various parts of I. javanica. HPLC technique is used to detect the presence and quantities of three flavonoids rutin, kaempferol and quercetin in the leaves and flowers and alkaloid camptothecin in the bark and roots of I. javanica. Rutin was best extracted (43.92%) using 90% ethanol whereas quercetin (0.27%) was best extracted using 85% methanol both from the flowers of the plant. Kaempferol was best extracted from leaves (1.15%) using petroleum ether as a solvent. Alkaloid camptothecin was found to be present in bark (7.34%) as well as root extracts (3.52%) of I. javanica. However, higher camptothecin content was present in the bark as compared to the roots of the same plant. Both 60% methanol or 60% ethanol were found to be equally good solvents for camptothecin extraction from bark and root samples. This is the first report of HPLC quantification of alkaloid camptothecin from the bark and roots of I. javanica.